2021
DOI: 10.1186/s40337-021-00495-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the experience of being viewed as “not sick enough”: a qualitative study of women recovered from anorexia nervosa or atypical anorexia nervosa

Abstract: Background Despite common misconceptions, an individual may be seriously ill with a restrictive eating disorder without an outwardly recognizable physical sign of the illness. The aim of this qualitative study was to investigate the perspectives of individuals who have previously battled a restrictive eating disorder who were considered “not sick enough” by others (e.g., peers, families, healthcare professionals) at some point during their illness, and to understand the perceived impact on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…Our results suggest that when physicians avoid asking about problematic substance use, this can lead the patient to trivialize the problem, “if you don’t talk about it, there is no problem” [AS7]. This echoes the “not sick enough” concept known in other behavioral disorders [ 37 ]. Furthermore, the patient’s resistance to discuss their addiction until they cross their own red line can frustrate physicians [ 38 , 39 ]: “when you ask the question but don’t get an answer, it’s easy to get impatient.…”
Section: Discussionmentioning
confidence: 57%
“…Our results suggest that when physicians avoid asking about problematic substance use, this can lead the patient to trivialize the problem, “if you don’t talk about it, there is no problem” [AS7]. This echoes the “not sick enough” concept known in other behavioral disorders [ 37 ]. Furthermore, the patient’s resistance to discuss their addiction until they cross their own red line can frustrate physicians [ 38 , 39 ]: “when you ask the question but don’t get an answer, it’s easy to get impatient.…”
Section: Discussionmentioning
confidence: 57%
“…In the work of Federici and Kaplan [ 52 ], participants (selected by BMI from among hospitalized patients) reported that a contributing factor to relapse was that their AN was no longer taken seriously following weight restorative treatment. With interviewees who had been diagnosed with AN, Eiring and colleagues [ 21 ] initiated critical dialogue exploring how stereotypes of AN feed into ‘not sick enough’ consequences, including dangers that materialize from “proof” of illness confirmation that becomes requisite for support. Their findings, in tandem with this current study, offer critical nuance to a perception that “the tragic and nearly universal reality for those with eating disorders is that they often believe they aren’t sick enough to warrant changing their behaviors or seeking help” [ 61 , p4].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we believe this approach strengthened the credibility and trustworthiness of the data given that “sharing personal information and divulging secrets more frequently than in face-to-face communications is one of the most consistent findings of anonymity studies” [ 51 , p5]. Further, we considered that respondents may have had previous disempowering evaluations of their bodies and appearance [ 21 , 52 ]. Respondents may bear heightened sensitivities towards power dynamics in methods that include in-person interactions and settings that emphasize researcher authority.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from our study allude to the possibility that, relative to those with AN, individuals with AAN may struggle more with certain ED symptoms after leaving PHP, despite showing continued improvements in weight. Research suggests that individuals with AAN experience a similar psychological presentation and impairment as those with AN (Eiring et al., 2021; Sawyer et al., 2016). However, individuals with AAN also live in higher‐weight bodies than those with AN.…”
Section: Discussionmentioning
confidence: 99%